Hubungan Gaya Belajar Dengan Keterampilan Berpikir Kritis Dan Kemampuan Kognitif Siswa Pada Mata Pelajaran Kimia di Kelas X SMKN 1 Bungku Tengah - Nurbaeti, Nurbaeti; Nuryanti, Siti; Pursitasari, Indarini Dwi (Mitra Sains, 2015)
This research aimed to describe correlation between: (1) learning style and critical thinking skill; (2) learning style and cognitive ability in chemistry subject; and (3) critical thinking skill and cognitive ability of students in chemistry subject at Class X of SMKN I Bungku Tengah. The population of the research was 48 students at Class X of SMKN I Bungku Tengah registered in 2013/2014 academic year. The sample of the research was the overall of the population member (saturated sample). The collecting data used questionnaire and multiple choice test. Data of the research were analyzed by using correlation and regression analyses. Based on the data analyses, it could be concluded that there were positive correlations between: (1) the learning style and the critical thinking skill; (2) the learning style and the cognitive ability; and (3) the critical thinking skill and the cognitive ability in chemistry subject of the students at Class X of SMKN IBungku Tengah.